1995
DOI: 10.1093/ajcp/104.5.574
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Glandular Cells of Undetermined Significance:Cytologic Criteria to Separate Clinically Significant From Benign Lesions

Abstract: Histologic follow-up of the cervical-vaginal smear diagnosis of atypical glandular cells of undetermined significance (AGUS) shows a broad spectrum of clinically significant (preneoplastic or neoplastic) and benign lesions. There are few statistical studies that have attempted to separate these AGUS categories based on select cytologic criteria. The authors retrospectively reviewed 116 AGUS without concurrent squamous dysplasia smears (66 clinically significant and 50 benign lesions), and used logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
107
0
10

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(122 citation statements)
references
References 0 publications
5
107
0
10
Order By: Relevance
“…The fourth cytopathologist (P.A.T) was a participant in several AGUS projects defining cytologic criteria for subclassification. 33 ' 34 This cytopathologist had made the original diagnosis in 7 cases but had not viewed these cases within 4 years. The cytopathologists were told that the study was designed to measure the interobserver variability of a diagnosis of AGUS, and they were not given any clinical history or follow-up information.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fourth cytopathologist (P.A.T) was a participant in several AGUS projects defining cytologic criteria for subclassification. 33 ' 34 This cytopathologist had made the original diagnosis in 7 cases but had not viewed these cases within 4 years. The cytopathologists were told that the study was designed to measure the interobserver variability of a diagnosis of AGUS, and they were not given any clinical history or follow-up information.…”
Section: Methodsmentioning
confidence: 99%
“…Two-way logistic regression analysis was used to determine the cytologic criteria that are important to individual cytopathologists in separating a clinically significant from a benign lesion. 34 To briefly summarize, variables to be entered into the logistic regression were identified through univariate analyses of association. These analyses were performed between the dependent variable (clinically significant lesion) and the presence or absence of each independent variable (cytologic criterion).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Before 2001, a spectrum of glandular cell abnormalities in cervical smears was grouped under atypical glandular cells of undetermined significance (AGUS) and defined as glandular cells exhibiting changes beyond reactive or reparative changes, but lacking unequivocal features of invasive adenocarcinoma. 2 The incidence and clinical significance of AGUS have been extensively reported, [3][4][5][6] however, studies reporting AGUS smears in pregnancy and postpartum period are very limited.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Surprisingly, histologic follow-up has shown that some of the clinically significant lesions are pure squamous dysplasias without glandular neoplasia.…”
mentioning
confidence: 99%